2011
DOI: 10.1007/s10803-011-1306-x
|View full text |Cite
|
Sign up to set email alerts
|

Service and Wider Societal Costs of Very Young Children with Autism in the UK

Abstract: Autism spectrum disorders (ASD) are associated with a substantial economic burden, but there is little evidence of the costs in the early years; the period in which children are increasingly likely to be diagnosed. We describe the services used by 152 children aged 24-60 months with autism, report family out-of-pocket expenses and productivity losses, and explore the relationship between family characteristics and costs. Children received a wide range of hospital and community services including relatively hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 13 publications
5
40
1
Order By: Relevance
“…However, one must take into account the differences in the concept of multiprofessional treatment between Brazil and the US when comparing data in both countries. In England, as cited above (Barrett et al, 2011), there is a predominance of speech and language therapies for autistic patients, and it is necessary to investigate whether such data is repeated in Brazil. In addition, since the data is based on information provided by the directors of the services, there may possibly be children and adolescents with autism whose simultaneous treatment with other professionals or at other institutions was not communicated to the CAPSi by their relatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one must take into account the differences in the concept of multiprofessional treatment between Brazil and the US when comparing data in both countries. In England, as cited above (Barrett et al, 2011), there is a predominance of speech and language therapies for autistic patients, and it is necessary to investigate whether such data is repeated in Brazil. In addition, since the data is based on information provided by the directors of the services, there may possibly be children and adolescents with autism whose simultaneous treatment with other professionals or at other institutions was not communicated to the CAPSi by their relatives.…”
Section: Discussionmentioning
confidence: 99%
“…In England, Barrett et al (2011) evaluated the use of services for preschool autistic children (24 to 60 months of age), with an emphasis on economic costs. The families of 152 children with autism were contacted to investigate the use of services in the six months prior to the interviews.…”
Section: Introductionmentioning
confidence: 99%
“…Child age is one of the most consistently identified factors associated with treatment selection for individuals with ASD ( Barrett et al, 2012;Goin-Kochel et al, 2007;Hebert, 2014;Shyu et al, 2010). Child age even has been shown to influence services offered in schools (i.e., which classroom-based strategies and school-based treatments; Hess, Morrier, Heflin, & Ivey, 2008).…”
Section: Child Age and Treatment Selectionmentioning
confidence: 99%
“…A national survey of parents of children with ASD and comorbid psychiatric conditions revealed that parents perceived the health outcomes of children with ASD and comorbid psychiatric conditions as poorer than children with ASD without psychiatric comorbidities (Ahmedani and Hock, 2012). Surveys of health-care expenditures of families of children with ASD indicate greater expenditures on total healthcare, total outpatient care, physician visits and prescription medicines (Barrett et al, 2012;Leslie and Martin, 2007;Liptak et al, 2006). The cost of ASD throughout the lifespan has been estimated at USD $3.2 million per capita, taking into account the impact of adult care and decreased productivity by individuals with ASD and their families (Ganz, 2007).…”
Section: Introductionmentioning
confidence: 99%